Hedonic sensitivity to natural rewards is affected by prenatal stress in a sex‐dependent manner. (26th May 2015) - Reynaert, Marie‐Line; Marrocco, Jordan; Mairesse, Jérôme; Lionetto, Luana; Simmaco, Maurizio; Deruyter, Lucie; Allorge, Delphine; Moles, Anna; Pittaluga, Anna; Maccari, Stefania; Morley‐Fletcher, Sara; Van Camp, Gilles; et al.
Abstract: Palatable food is a strong activator of the reward circuitry and may cause addictive behavior leading to eating disorders. How early life events and sex interact in shaping hedonic sensitivity to palatable food is largely unknown. We used prenatally restraint stressed (PRS) rats, which show abnormalities in the reward system and anxious/depressive‐like behavior. Some of the hallmarks of PRS rats are known to be sex‐dependent. We report that PRS enhanced and reduced milk chocolate‐induced conditioned place preference in males and females, respectively. Male PRS rats also show increases in plasma dihydrotestosterone (DHT) levels and dopamine (DA) levels in the nucleus accumbens (NAc), and reductions in 5‐hydroxytryptamine (5‐HT) levels in the NAc and prefrontal cortex (PFC). In male rats, systemic treatment with the DHT‐lowering drug finasteride reduced both milk chocolate preference and NAc DA levels. Female PRS rats showed lower plasma estradiol (E2 ) levels and lower DA levels in the NAc, and 5‐HT levels in the NAc and PFC. E2 supplementation reversed the reduction in milk chocolate preference and PFC 5‐HT levels. In the hypothalamus, PRS increased ERα and ERβ estrogen receptor and CARTP (cocaine‐and‐amphetamine receptor transcript peptide) mRNA levels in males, and 5‐HT2 C receptor mRNA levels in females. Changes were corrected by treatments with finasteride and E2, respectively. These new findings show that early life stress has a profound impact on hedonic sensitivity to high‐palatable food via long‐lasting changes in gonadal hormones. This paves the way to the development of hormonal strategies aimed at correcting abnormalities in the response to natural rewards. Abstract : We report that prenatal restraint stress enhances the rewarding properties of a natural reward in male rats, while exerting an opposite effect in females. Changes in hedonic sensitivity to milk chocolate are tightly dependent on changes in gonadal hormones (dihydrotestosterone in males, estradiol in females). Physiological or pharmacological modifications of the hormonal status affect sensitivity to palatable food and related changes in neurobiological substrates: dopamine in the nucleus accumbens of males and serotonin in the prefrontal cortex of females.